Repräsentationen der israelischen Soldatin im Netz der Bildkulturen - Radjai-Bründl, Jihan Jennifer (Heidelberg University Publishing (heiUP), 2022)
Representations of female Israeli soldiers are a popular subject in photography. However, a notable controversial imparting exists concerning gender and identity: heroic depictions of female Israeli soldiers as shown by the Israeli military in their official representations are in contrast to portraits which are either sexualized or appear as a form of criticism on military service as such and the responsibility of young women soldiers towards the state and the people. This analysis focusses on aspects of the visual language and aesthetics in the context of the cultural history discourse of Zionism, as well as on stereotypes such as the ›beautiful Jewess‹ in European painting since the 18th century. The results offer a unique contribution to Jewish studies by combining methods of gender studies and art history, as well as visual studies.